2020
DOI: 10.24187/ecostat.2020.517t.2017
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Deflators for Telecommunications Services Output

Abstract: The opinions and analyses in this article are those of the author(s) and do not necessarily reflect their institution's or Insee's views.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…The aggregate estimate is from Corrado (2020, 2021), which applies to the United States and covers mobile voice and data, internet access, cable TV, and video streaming. This estimate is consistent with results showing comparably rapid rates of price drops for mobile voice and data in the United Kingdom by Abdirahman, Coyle, Heys, and Stewart (2020) and for music streaming globally by Edquist, Goodridge, and Haskel (2021).…”
Section: Growth Decompositions Growth Decompositionssupporting
confidence: 90%
“…The aggregate estimate is from Corrado (2020, 2021), which applies to the United States and covers mobile voice and data, internet access, cable TV, and video streaming. This estimate is consistent with results showing comparably rapid rates of price drops for mobile voice and data in the United Kingdom by Abdirahman, Coyle, Heys, and Stewart (2020) and for music streaming globally by Edquist, Goodridge, and Haskel (2021).…”
Section: Growth Decompositions Growth Decompositionssupporting
confidence: 90%
“…In terms of magnitude these price drops seem large, but they are comparable to price indices reported for telecommunication services (Abdirahman et al , 2017) and smartphones (Byrne, Sichel and Aizcorbe, 2019).…”
Section: Measuring Cloud Computing Servicessupporting
confidence: 66%
“…A range of services are delivered over networks, and dataflows/IP traffic may not always be the relevant indicator of quality, but for internet access services via computers of mobile phones IP traffic would appear to be a solid choice (e.g., see Abdirahman, Coyle, Heys, and Stewart, 2017). For video services, quality is not so simple; cross-country studies have found that the quality dimension for video services is captured by a range of controls, including the number of channels (HD and standard), and availability of premium channels and 4K display resolution (Corrado andUkhaneva, 2016, 2019;Díaz-Pinés and Fanfalone, 2015).…”
Section: Paid-for Servicesmentioning
confidence: 99%